Annual Review 2008 - Kahl, Dan; Hoch, Connie; Stinson, Jeanne; Burton, Josh (My University, 2008)
Summary of the 2008 actiivities of the Kansas PRIDE program and affiliated communities.
Keywords: Administrative and Research Reports; Community Development